2017
DOI: 10.1136/bcr-2017-220427
|View full text |Cite
|
Sign up to set email alerts
|

Vesical dermoid: a rare bladder tumour

Abstract: Dermoid cysts are benign developmental lesions consisting of tissues of more than one germ cell lineage origin. The urinary bladder is a very rare location of dermoid cysts. We report a case of an 18-year-old woman who presented with suprapubic pain, dysuria and turbid urine. Blood and serum chemistry was normal. Contrast-enhanced CT revealed a heterogeneously enhancing mass of 2.5×2 cm within the urinary bladder infiltrating fundus of urinary bladder with extraluminal extension. At cystoscopy, an irregular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Maximum decrease of 14.97 % is obtained at 0.3 % volume concentration upon use of bent tube. (6). Friction factor increases with rise in nanoparticle concentrations and decreases with rise in Reynolds number.…”
Section: Conclusive Remarksmentioning
confidence: 95%
See 1 more Smart Citation
“…Maximum decrease of 14.97 % is obtained at 0.3 % volume concentration upon use of bent tube. (6). Friction factor increases with rise in nanoparticle concentrations and decreases with rise in Reynolds number.…”
Section: Conclusive Remarksmentioning
confidence: 95%
“…Almost every study conducted after introduction of nanofluids terminology have reported significant amount of enhancement in performance of conventional heat transfer fluids [3][4][5][6][7][8]. Heris et al [9] reported in their study of Al2O3/water nanofluids flowing through circular tube that heat transfer coefficient increased with increase in volume concentration of nanoparticle from 0.2 % to 2.5 % with Reynolds number varying in between 700 and 2050.…”
Section: Introductionmentioning
confidence: 99%